Use of Indonesian in Financial Reports for Investor Understanding - Br. Tarigan, Gita Mori Savira; Naibaho, Hesly Irawanda; Saragih, Kevin Jeremi Doniartha; Nasution, Rendinova Cahyadi; Zebua, Seniman Hati; Ayu Nadira Wulandari (Yayasan Salam Cerdas Al-Fattah, 2024)
This paper aims to provide a comprehensive overview of the use of Indonesian language in an effort to improve investor understanding, especially related to financial reports. By using the library research method, this paper presents complete information based on relevant primary data. Through an in-depth analysis of the existing literature, this study emphasizes the importance of using clear, concise, and contextual language in financial reports as an effective means of communication between companies and investors. This study also reveals that the use of proper Indonesian language not only helps investors understand complex financial information but also contributes to the formation of trust and transparency. By understanding accurate terminology and presentation, investors can make more informed investment decisions, which can ultimately increase their participation in the market. Finally, this paper emphasizes that Indonesian language acts as a bridge connecting companies with investors, making it a key component in effective financial reports. It is hoped that the results of this study can contribute to better accounting practices and improve financial communication among various stakeholders. Through a better understanding of language use, it is hoped that companies can achieve success and sustainability in an increasingly competitive business environment